Changes in national competitiveness of the Czech Republic according to the Global Competitiveness Report - Sládková, Aneta; Nečadová, Marta; Breňová, Lubomíra, 1948-2025; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The thesis focuses on the evaluation of the competitiveness of the Czech Republic based on the annual reports of the World Economic Forum. The primary aim of the thesis is to analyze the results of the Czech Republic according to the Global Competitiveness Report in comparison with the average of the member states of the European Union. Another aim is to evaluate the impact of the applied methodology on country results. The theoretical part of the thesis introduces different approaches to the concept of national competitiveness, including a critical point of view on its meaningfulness. The following part contains a description of the construction of composite indicators that the World Economic Forum uses as a tool for measuring competitiveness. Subsequently, the current methodology of the World Economic Forum and a new proposal of the new WEF’s methodology – the GCI 4.0 are presented. The analytical part presents the results of the Czech Republic and EU-28 in measured areas in the last ten years and the differences in values of composite indicators caused by the application of different aggregation methods.
Vedoucí práce: Marta Nečadová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses